Paleolimnological Evidence of Terrestrial and Lacustrine Environmental Change in Response to European Settlement of the Red River Valley, Manitoba and North Dakota - Medioli, Barbara; Dixit, Aruna; Smol, John; Anderson, Thane; Burbidge, Susan (Géographie physique et Quaternaire, 2005)
AbstractLimnological and terrestrial changes in three floodplain lakes are correlated with settlement of the Red River valley in Manitoba and North Dakota. Distinctive pollen, diatom and thecamoebian assemblages provide proxy evidence of the ecological changes from pre- to post-settlement periods in Horseshoe Lake, Lake Louise and Salt Lake. In the pre-settlement period (Zone I), prior to ~1812, grass and Quercus pollen dominate and are indicative of a tall grass prairie-oak riparian forest ecosystem. Diatom and thecamoebian assemblages suggest oligo- to mesotrophic limnological conditions, and more brackish water than presently occurs in Horseshoe Lake. The onset of the post-settlement period (Zone II) corresponds to distinctive terrestrial and limnological changes. A sharp decline in Quercus at the base of this zone correlates with documented regional riparian deforestation, whereas the increase in the weed taxa Salsola, Brassica, Rumex and Ambrosia is associated with the introduction of European agricultural practices and cereal grasses. Diatom and thecamoebian assemblages indicate progressive floodplain lake eutrophication, as well as increased salinity in Salt Lake. Salt Lake is the most brackish lake and supports the brackish-water foraminifera Trochammina macrescens cf. polystoma. Increased erosion and run off in the watershed has caused a more than twofold increase in lake basin sedimentation between the pre-settlement and post-settlement periods.